THE RELATIONSHIP BETWEEN RELIGIOSITY AND CELEBRITY WORSHIP BEHAVIOR AMONG TEENS - Dewi Sartika; Marhani, Marhani; Nurhayati, Andi (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
This study aims to explore the relationship between religiosity and celebrity worship behavior among adolescents. With the increasing influence of media and celebrity culture, the phenomenon of celebrity worship—excessive affection for celebrities—has become a significant concern in social psychology research. Religiosity, which encompasses the intensity and commitment to religious beliefs, plays an important role in shaping individual values and behaviors; however, its impact on celebrity worship is not fully understood. This research employs a quantitative method with a correlational design to evaluate the relationship between levels of religiosity and celebrity worship behavior, focusing on adolescents aged 15-17 through purposive sampling. Data collection was conducted using an online questionnaire and analyzed using Pearson product-moment correlation. The results indicate a correlation between religiosity and celebrity worship behavior with a correlation coefficient of 0.392%. These findings provide important insights into how religious values can minimize adolescents' tendencies to engage in celebrity worship behavior.